THE INFLUENCE OF SKILLS TRAINING ON THE WORK READINESS OF STUDENTS OF VOCATIONAL SCHOOL 1 PALANGKA RAYA CITY IN THE CONSTRUCTION INDUSTRY - Ni Putu Diah Agustin Permanasuri; Mega Kurniawati; Tuah; Clara Olivia (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
This research aims to analyze the effect of skills training on the work readiness of Vocational High School (SMK) students in the construction industry. Even though many vocational school students have completed their education, in reality many are not ready to enter the world of work, especially in the construction sector which requires strong technical skills and professional attitudes. Therefore, skills training, including work-based learning (WBL) models, is important in preparing students to meet industry needs. The results of this research indicate that relevant and intensive skills training can improve students' competency and work readiness, although there are variations in the effectiveness of the training programs implemented.